Downsizing : is less still more? - Cooper, Cary L.; Pandey, Alankrita; Quick, James C. (New York : Cambridge University Press, 2012)
'Downsizing is one of the most frequently used business strategies for reducing costs, returning firms to profit or for restructuring businesses following takeovers, mergers and acquisitions. Downsizing measures are also set to become much more prevalent in the public sector as governments seek to restrict levels of public spending. This book is one of the first to provide a thorough study of downsizing from a global perspective. It examines the phenomenon in its entirety, exploring how it is initiated and what the process of downsizing looks like. It also looks at the effects of downsizing at a number of different levels, from the individual (e.g., motivational effects, effects on health and stress levels) to the organizational (e.g., financial outcomes, reputational and productivity outcomes). Written by an international team of experts, the book provides a comprehensive overview of downsizing that examines both the strategic and human implications of this process.'--Publisher.
Job loss and effects on firms and workers / Kevin F. Hallock, Michael R. Strain, and Douglas Webber -- How does downsizing come about? / Wayne F. Cascio -- The antecedents of downsizing / Sarah J. Freeman and Kyle Ehrhardt -- Human motivation and performance outcomes in the context of downsizing / Aharon Tziner, Erich C. Fein, and Lior Oren -- To downsize human capital : a strategic human resource perspective on the disparate outcomes of downsizing / Gary C. McMahan, Alankrita Pandey, and Brian Martinson -- Health effect outcomes :'survivor disease' in the context of economic change / Johannes Siegrist and Nico Dragano -- Employee downsizing and organizational performance : what do we know? / Deepak K. Datta, Dynah A. Basuil, and Elena A. Radeva -- Executive perceptions : probing the institutionalization of organizational downsizing / William McKinley and Jasmin Chia-Jung Lin -- Reducing costs and enhancing efficiency or damaging the company : downsizing in today's global economy / Kenneth P. de Meuse and Guangrong Dai -- The stress outcomes of downsizing / M. Blake Hargrove, Cary L. Cooper, and James Campbell Quick -- Good downsizing / Rocki-Lee Dewitt -- Post-downsizing implications and consequences : a global perspective / Franco Gandolfi ... [et al.] -- Exploring the etiology of positive stakeholder behavior in global downsizing / Shay S. Tazfrir, Hila Chalutz Ben-Gal, and Simon L. Dolan.
Includes bibliographical references and index.
Keywords: Downsizing of organizations